Radiation induced nanovoid shrinkage in Cu at room temperature: An in situ study. (June 2019) - Fan, C.; Sreekar, A.R.G.; Shang, Z.; Li, Jin; Li, M.; Wang, H.; El-Azab, A.; Zhang, X.
Abstract: Radiation induced void swelling is widely observed in a variety of metallic materials. Here, by using sputtering deposition technique, we have introduced faceted nanovoids into Cu films. In-situ Kr ion irradiation was subsequently performed at room temperature to investigate the evolution of nanovoids. Most nanovoids found to shrink gradually with increasing dose. Irradiation induced high-density vacancy clusters exist mostly in the form of stacking fault tetrahedrons. Phase field modeling reveales that void shrinkage arises from biased absorption of interstitials. These findings provide insights to the physical mechanisms of radiation response of nanovoids in metallic materials. Graphical abstract: Unlabelled Image